Antimicrobial effect of sugar osazones and anhydro sugars - Zemek, J; Linek, K; Kadlecíková, B; Kucár, S; Somogyi, L (Folia microbiologica, 1985)
The antimicrobial effect of 14 sugar osazones and anhydro sugars was studied with model strains of Micrococcus luteus, Bacillus licheniformis, Escherichia coli and strains Staphylococcus aureus and Pseudomonas aeruginosa isolated from clinical material. The relationship between the structure of these compounds, their solubility in water and 1-octanol and antimicrobial effect was investigated.
Keywords: Staphylococcus aureus; Bacteria; Hexoses; hydrazony; Micrococcus; Solubility; rozpustnost; vztahy mezi strukturou a aktivitou; Pseudomonas aeruginosa; Structure-Activity Relationship; hexosy; Hydrazones; Bacillus; Escherichia coli